Pendidikan Politik Islam melalui Media Sosial dalam Meningkatkan Partisipasi Warga pada Pemilihan Presiden Tahun 2024 - Zainuddin T (Sadida Islamic Communications and Media Studies, 2024)
This research explores the urgency of Islamic political education through social media in shaping citizens' understanding of Islamic values. The research approach uses qualitative methods and content analysis by taking data from interviews and social media platforms such as WhatsApp, Instagram and YouTube. Through a qualitative approach, this research answers key questions related to the urgency of Islamic political education, the impact of social media, and citizen participation in the presidential election process. The Humanistic Theory of Political Education is the basis for understanding how Islamic political education can shape citizen understanding and participation. The research results show that social media is an effective channel for spreading Islamic political education. Islamic political education through social media has a strategic role in shaping citizens' understanding and participation in the presidential election. The implications of this research can be used to improve the quality of Islamic political education and utilize social media as an effective tool for spreading Islamic values in the political realm.